ASSESSMENT EFFECTIVENESS ANALYSIS SYSTEM USING G-FORM WITH TAM METHOD AT SD GALATIA3 JAKARTA BARAT - Asrul Sani; Agus Budiyantara; Rizaldy Khair; Siti Aisyah (Kresnamedia Publisher, 2022)
In late December 2019 it took the world by storm by transmitting very quickly through the human respiratory tract. Since this happened the World Health Organization (WHO) has stated that Covid-19 is called a pandemic. The Covid-19 outbreak affects almost all aspects of life, including the aspect of education in Indonesia, which is also not spared from the Covid-19 outbreak and also feels the consequences of the spread of the virus. Students feel the impact of the spread of Covid-19 such as changes in the provision of services in educational institutions, such as formal education at all levels, non-formal education, to academics (Baety and Munandar 2021). Based on the announcement of the Ministry of Education and Culture Number 4 of 2020 concerning the Implementation of Education Policies during the Emergency Period of the Spread of the Coronavirus (Covid-19). The government began to implement an online learning system (online). The problem that arises during this online learning period is that there are still many people who are not ready to face technology, both in terms of teachers and students, this happened in the early days of the pandemic. So that the learning process that has been carried out normally, both in terms of teaching and providing assessments, also experiences obstacles. This is because the teaching staff (teachers) always have daily assessment data that is usually carried out daily during normal learning. However, during this PJJ period, teachers became confused about giving daily assessments to their students. The purpose of the research is to analyze and evaluate the online learning system using a platform that is easy to operate by teachers and can be accessed anywhere, namely, google form. In the Google Form application, there is an automatic calculation system in the form of student feedback where teachers do not bother to manually calculate the results of student learning evaluations (Munawaroh, Prastowo, and Nurjanah 2021). The analysis method used is the Technology Acceptance Model (TAM) which is able to find out the attitudes of users towards the technology used, so that teachers can easily find out whether the tasks given to students are done by the students themselves, not the help of parents.